Wage discrimination against immigrants: Measurement with firm-level productivity data - Stephan Kampelmann; François Rycx (IZA Journal of Migration, 2016)
This paper is one of the first to use employer-employee data on wages and labor productivity to measure discrimination against immigrants. We build on an identification strategy proposed by Bartolucci (Ind Labor Relat Rev 67(4):1166-1202, 2014) and address firm fixed effects and endogeneity issues through a diff GMM-IV estimator. Our models also test for gender-based discrimination. Empirical results for Belgium suggest significant wage discrimination against women and (to a lesser extent) against immigrants. We find no evidence for double discrimination against female immigrants. Institutional factors such as firm-level collective bargaining and smaller firm sizes are found to attenuate wage discrimination against foreigners, but not against women.
Keywords: J15; J16; J24; J31; J7; 330; Wages; Productivity; Discrimination; Workers' origin; Gender; Linked employer-employee panel data